Variabilidade dos elementos energéticos e ambientes em meio protegido com polietileno, sem e com cultura do pimentão (Capsicum annuum L.) - Silva, Marcelo Augusto de Aguiar e [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
O experimento foi desenvolvido na área experimental do Departamento de Recursos Naturais – Setor Ciências Ambientais da Faculdade de Ciências Agronômicas, UNESP, Campus de Botucatu, SP. Neste trabalho avaliaram-se os elementos energéticos (radiação solar global, refletida, difusa, coeficiente de reflexão, saldo de radiação de ondas curtas e fluxo de calor no solo) e ambientais (temperatura do solo, temperatura e umidade relativa do ar), nas condições de ambiente protegido e campo, e o índice de cada um desses elementos, em dois períodos coincidentes de 97 dias, em anos diferentes, sem cultura (01/06 a 05/09/99) e com cultura do pimentão híbrido Margarita (01/06 a 05/09/00). A área experimental constitui-se de duas parcelas, com dimensões e sentido idênticas, uma representando a condição de ambiente protegido e a outra a condição de campo. O ambiente protegido utilizado, foi do tipo arco não-climatizada, com área de 140 m2, coberta com polietileno de 100mm de espessura e nas laterais utilizou-se malha preta de polietileno (sombrite) com redução de 50% da radiação solar global, orientado predominantemente na direção leste-oeste geográfico... .

The experiment was carried out at the experimental area of the Departmento de Recursos Naturais – Área de Ciências Ambientais of Faculdade de Ciências Agronômicas, UNESP, Botucatu, SP. It was evaluated the energy (global radiation, reflected, diffuse, reflection coefficient, short waves radiation balance and soil heat flow) and environmental elements (soil temperature, temperature and air relative humidity), in the conditions of protected atmosphere and on the field, and the index of each one of those elements, in two coincident periods of 97 days, in different years, without culture (01/06 to 05/09/99) and with hybrid bell pepper crop Margarita (01/06 to 05/09/00). The experimental area is constituted of two portions, with dimensions and identical directions, the greenhouse and the field condition. The greenhouse was of arch type, no-acclimatized, with 140 m2, covered with 100mm thickness polyethylene and black polyethylene net with 50% of the solar radiation reduction in the lateral, guided predominantly in the east-west geographical direction. The results showed that: the) The global radiation index was higher in the bell pepper crop period, due mainly to the different atmospheric conditions at the determination moment and to the covering material time of exposure to the environmental conditions, the difference being not related directly to a crop effect on the cultivation microclima; b) The bell pepper crop reflection coefficient presented lower values than the soil reflection coefficient, due to traps formed by the leaves that arrested part of the reflected radiation; c) The index of the reflected radiation and of the reflection coefficient presented higher values in the crop period, but that increase is not related to an effect of bell pepper crop in the cultivation microclima. The variation of that index in the crop period is related to the bell pepper leaf area index... (Complete abstract, click electronic address below).
Keywords: Climatologia agricola; Pimentão